2021
DOI: 10.29333/iji.2021.14448a
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing of Math Adversity Quotient in Mathematics Cooperative Learning Through Metacognitive

Abstract: Students' success in learning is inseparable from their high level of fighting power or the Adversity Quotient (AQ) they have. This study examines whether there was an Adversity Quotient (AQ) difference between Boarding Schools (BS) and Non-Boarding Schools (NBS) students through the application of metacognitive learning Think-aloud cooperative setting through the application of metacognitive learning Think-aloud cooperative setting Think-Pair-Share (MTPS), Think-Pair Square (MTPQ), and Conventional Class (CC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…The development of learning tools has been carried out to the maximum with the right procedures so that the experts state that the learning tools can be used according to the purpose. The development of learning devices that are carried out optimally can provide maximum contribution to learning (Amir et al, 2021;Maclinton & Andrian, 2022;Risnawati et al, 2019). Paying attention to the right procedures in the development of learning tools is an important requirement to produce quality products (Rezeki et al, 2021;Wahyuni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of learning tools has been carried out to the maximum with the right procedures so that the experts state that the learning tools can be used according to the purpose. The development of learning devices that are carried out optimally can provide maximum contribution to learning (Amir et al, 2021;Maclinton & Andrian, 2022;Risnawati et al, 2019). Paying attention to the right procedures in the development of learning tools is an important requirement to produce quality products (Rezeki et al, 2021;Wahyuni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the researcher's interview with the mathematics study teacher at Al-Manar Pekanbaru on 7 July 2020 on mathematics learning tools, some information was obtained as follows; 1) there is a discrepancy between learning objectives and indicators of competency achievement, 2) the LIP used by the teacher has not presented detailed time allocations for each learning activity, 3) the learning steps in the LIP still describe the teacher-centered learning process, 3) the LIP is used by the teacher has not included an answer key for knowledge assessment questions 4) The LIP used by the teacher has not included an assessment rubric for skills assessment questions, 5) The teacher has never provided lesson plans using a learner-centered learning model; 6) Teachers often use SAS available from book publishers, so that learning mathematics in class seems monotonous and does not vary; 7) The SAS presented by the teacher only contains a summary of the material and practice questions, so that it is difficult for students to understand the lesson; 8) In SAS there is no empty space for students to write answers; 9) Does not contain pictures/illustrations that interest students to work on SAS; 10) The SAS presented by the teacher in terms of design and color is not attractive, so that students are not motivated in learning mathematics; 11) The teacher has never provided Ethnomathematics-based math SAS. Amir et al, (2021) & Risnawati et al, (2019 stated that it is difficult for teachers to manage time because of the high teaching load, so it is difficult to develop SAS that can assist teachers in teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, students can better understand what they have learned and aims to study to map learning problems better. Meanwhile, Amir et al (2021) have introduced metacognitive to enhance the adversity quotient in mathematics learning through a thinkaloud strategy. This study found that metacognition increased awareness and thought efforts in solving complex problems.…”
Section: Introductionmentioning
confidence: 99%
“…The teaching and learning process are activities built by teachers to develop students' abilities to understand and manage creative thinking, thinking skills, and construct new knowledge [1], [2]. Critical thinking is one of the objectives of learning mathematics, namely the formation of reasoning abilities in students, which is reflected through critical, logical, systematic thinking, and able to have an objective nature, be honest and disciplined to solve problems both in learning mathematics and other learning, and in everyday life day [3].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Curiosity arises, eager to learn, has self-confidence, and a high willingness to mathematics, (3) The emergence of a sense of self-awareness about the importance of learning mathematics, which is formed and formed from the learning experience, (4) Have a spirit that likes to discuss, be objective during group interactions or in daily activities (5), Have the ability to communicate mathematical ideas clearly, and (6) Identify patterns and use them to guess general rules and provide predictions [4]. Point number (1) Given the importance of MCTS in the mathematics learning, it requires a teacher to be able to apply mathematics learning that can improve students' MCTS [1], [2]. This is because, based on the results of observations and field facts, it was find facts about students' low mathematical critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%